Validity and Practicality of Articulate Storyline Learning Media on Environmental Pollution Materials for Junior High School Students - Maya Istyadji; Ratna Yulinda; Dina Amalina; Fahmi (Jurnal Penelitian Pendidikan IPA, 2022)
Research has been carried out on the development of Articulate storyline on environmental pollution material. This study aims to test the validity and practicality of the Articulate storyline on environmental pollution material. The development model used in this research is the ADDIE development model up to the implementation stage. The instruments used in this study were validation sheets and student response questionnaires. The results of this study obtained high validity criteria with a value of 0.90. The results of the practicality of this study get very practical results with an average value of 95.5%. The product resulting from this research can be continued to the effectiveness stage.